Review of Anaphes Haliday (Hymenoptera: Mymaridae) with key to species in Europe and a world catalogue - Huber, John T.; Thuróczy, Csaba (Zootaxa, 2018)
The Walter Soyka species of Anaphes Haliday are reviewed and placed in context among the remaining world species. An analysis of his descriptions and identification keys is presented, and discussed in light of a broader interpretation of intraspecific variation in Anaphes species than Soyka accepted. An illustrated diagnosis of Anaphes is given and the species in Europe considered to be valid are keyed—14 species in Anaphes (Anaphes) and 15 species in Anaphes (Patasson). The 244 names of world Anaphes are tabulated in various ways and their type localities, if known, are mapped. All available valid names and their synonyms, mostly from among the 155 nominal species described by Soyka, are catalogued, with details of type material and collecting information. A total of 167 synonyms are listed, 17 of which are synonyms proposed by earlier authors and 149 of which are proposed as new synonyms. Lectotypes are designated for Mymar ferreirei Soyka and Yungaburra acutiventris Soyka. Nine nomina dubia, 2 names of fossil species that most likely do not belong to Anaphes, 3 unavailable names and 20 species transferred to other genera are listed separately; among the latter, Anagrus foersteri (Ratzeburg) is transferred to Erythmelus Enock as E. foersteri (Ratzeburg), comb. n. Host records published from 1985–2015 are tabulated; most are from the literature but a few are from unpublished records found on slide mounted Anaphes specimens in various collections, mostly in Europe. The merits of classifying the available names of nominal species into an earlier classification with subgenera Anaphes (Anaphes) and Anaphes (Patasson) instead a later classification consisting of species groups within Anaphes (Anaphes) and Anaphes (Yungaburra) are discussed; the earlier classification is preferred.